Localization and Pattern of Graviresponse across the Pulvinus of Barley Hordeum vulgare - Brock, Thomas G. (1989)
Pulvini of excised stem segments from barley (Hordeum vulgare cv `Larker') were pretreated with 1 millimolar coumarin before gravistimulation to reduce longitudinal cell expansion and exaggerate radial cell enlargement. The cellular localization and pattern of graviresponse across individual pulvini were then evaluated by cutting the organ in cross-section, photographing the cross-section, and then measuring pulvinus thickness and the radial width of cortical and epidermal cells in enlargements of the photomicrographs. With respect to orientation during gravistimulation, we designated the uppermost point of the cross-section 0° and the lowermost point 180°. A gravity-induced increase in pulvinus thickness was observable within 40° of the vertical in coumarin-treated pulvini. In upper halves of coumarin-treated gravistimulated pulvini, cells in the inner cortex and inner epidermis had increased radial widths, relative to untreated gravistimulated pulvini. In lower halves of coumarin-treated pulvini, cells in the central and outer cortex and in the outer epidermis showed the greatest increase in radial width. Cells comprising the vascular bundles also increased in radial width, with this pattern following that of the central cortex. These results indicate (a) that all cell types are capable of showing a graviresponse, (b) that the graviresponse occurs in both the top and the bottom of the responding organ, and (c) that the magnitude of the response increases approximately linearly from the uppermost point to the lowermost. These results are also consistent with models of gravitropism that link the pattern and magnitude of the graviresponse to graviperception via statolith sedimentation.